Molecular and Functional dissection of IgaA, the negative regulator of the E.coli Rcs system. - Hussein, Nahla A. (AUC Knowledge Fountain, 2019)
The cell envelope of Gram-negative bacteria is a complex macromolecular structure, performing essential functions such as transport, respiration and protection. Moreover, it is the first line of contact between bacteria and their surroundings. Thus, maintenance of the cell envelope homeostasis is essential for bacterial survival and adaptation. In enterobacteria, the Rcs system (Regulator of capsule synthesis) monitors envelope integrity and induces a stress response when damages occur in the outer membrane or in the peptidoglycan layer. Built around a two-component system, Rcs controls gene expression via a cascade of phosphoryl transfer reactions. Being particularly complex, Rcs also involves the outer membrane lipoprotein RcsF and the inner membrane essential protein IgaA (Intracellular growth attenuator). RcsF is the stress sensor of the Rcs system while IgaA is the negative regulator, maintaining a minimal activation of the Rcs system in the absence of specific cues. Here, we establish the stress-dependent formation of a complex between RcsF and the periplasmic domain of IgaA as the molecular signal triggering Rcs, in the presence of cell-envelope targeting antibiotics. Moreover, molecular dissection of IgaA reveals that its negative regulatory role on Rcs is mostly carried by its first N-terminal cytoplasmic domain. Our analysis revealed also a contribution of IgaA transmembrane domains in its negative regulatory function. Altogether, our results support a model in which IgaA regulates Rcs activation by playing a direct role in the transfer of signals from the cell envelope to the cytoplasm. This remarkable feature further distinguishes Rcs from other envelope stress response systems and pave the way for the understanding of the molecular mechanism of the Rcs system.